LINKING ECOLOGICAL AND SOCIAL RESPONSIBILITY - SOCIAL PLASTIC AS A POSSIBLE SOLUTION? - Mélypataki, Gábor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Sustainable economy is a complex issue that requires active or even proactive behaviour from all actors. The state must use its own instruments to coordinate market processes, fight against socio-political problems and try to enforce certain human rights in parallel. In this way, it is natural that the state would also like to be relieved of its burdens of liability. The question is to what extent it can do so. Especially on such issues as environment and the fight against poverty? To what extent can CSR (corporate social responsibility) activities by businesses or PSR (public social responsibility) activities by public authorities be enforced, and within what social and legal framework? Who is responsible and to what extent? In our study, we will examine this at the level of theory and practice. To illustrate practice, we would like to present the Social Plastic project as a good practice.